Proteomic insights into extracellular matrix dynamics in the intestine of Labeo rohita during Aeromonas hydrophila infection - Nissa, Mehar Un; Pinto, Nevil; Ghosh, Biplab; Banerjee, Anwesha; Singh, Urvi; Goswami, Mukunda; Srivastava, Sanjeeva (mSystems, 2024)
In the aquaculture sector, one of the challenges includes disease outbreaks such as bacterial infections, particularly from Aeromonas hydrophila (Ah), impacting both wild and farmed fish. In this study, we conducted a proteomic analysis of the intestinal tissue in Labeo rohita following Ah infection to elucidate the protein alterations and its implications for immune response. Our findings indicate significant dysregulation in extracellular matrix (ECM)-associated proteins during Ah infection, with increased abundance of elastin and collagen alpha-3(VI). Pathway and enrichment analysis of differentially expressed proteins highlights the involvement of ECM-related pathways, including focal adhesions, integrin cell surface interactions, and actin cytoskeleton organization. Focal adhesions, crucial for connecting intracellular actin bundles to the ECM, play a pivotal role in immune response during infections. Increased abundance of integrin alpha 1, integrin beta 1, and tetraspanin suggests their involvement in the host’s response to Ah infection. Proteins associated with actin cytoskeleton reorganization, such as myosin, tropomyosin, and phosphoglucomutase, exhibit increased abundance, influencing changes in cell behavior. Additionally, upregulated proteins like LTBP1 and fibrillin-2 contribute to TGF-β signaling and focal adhesion, indicating their potential role in immune regulation. The study also identifies elevated levels of laminin, galectin 3, and tenascin-C, which interact with integrins and other ECM components, potentially influencing immune cell migration and function. These proteins, along with decorin and lumican, may act as immunomodulators, coordinating pro- and anti-inflammatory responses. ECM fragments released during pathogen invasion could serve as “danger signals,” initiating pathogen clearance and tissue repair through Toll-like receptor signaling.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Aeromonas hydrophila; extracellular matrix; focal adhesion; gut proteo mics; mass spectrometry; rohu